Election Offences as the Ground of Election Petition: A Comparative Analysis - Santoso, Topo (UI Scholars Hub, 2007)
This article is intended to compare the regulation about the criminal offence of general elections to be able to file a lawsuit. The main question is what is the legal basis to file a general election lawsuit in Indonesia, Malaysia, Singapore, and Philippine. Does the criminal offence of general elections be the one reason for having a general election lawsuit? In this research proved that in Indonesia the legal basis of the general election lawsuit only the presence of error of the counting the general election results by the Commission of General Election (KPU), so the general election cannot be used for the legal basis to file a lawsuit. It is different with the regulation in another country whose the criminal offence of general election can be the legal basis to file a lawsuit.